PENGEMBANGAN PERANGKAT PEMBELAJARAN MATA KULIAH KALKULUS LANJUT 1 DENGAN SCAFFOLDING BERBASIS KEMAMPUAN PEMECAHAN MASALAH - Muhtarom .; Sugiyanti .; Dhian Endahwuri (Media Penelitian Pendidikan : Jurnal Penelitian dalam Bidang Pendidikan dan Pengajaran, 2015)
The aims of this research was to develop learning device of Advanced Calculus 1 subject with scaffolding-based problem-solving abilities that include syllabi, lesson plan, learning media, student worksheets and assessment, and determine the effectiveness of the implementation of scaffolding-based learning problem-solving abilities in the subject Advanced Calculus 1.This research was a Research and Development (R & D). Methods of data analysis done by using triangulation mix-design method by simultaneously analyze data from quantitative and qualitative data as well as data combined. The results showed that the development of the learning course Advanced Calculus 1 with scaffolding based problem solving ability using learning device development of Borg and Gall models which has been modified. Results of learning device development course Advanced Calculus 1 consists of a syllabi, lesson plan, student worksheet, observation sheets and feasible achievement test used. Furthermore limited trial obtained tvalue ?»Ôé¼?¢7,440 ?»Ôé¼?¥ttable ?»Ôé¼?¢1,645so H0 is rejected. This shows that the average learning outcomes with scaffolding better than conventional learning. ?é?á Key words : Scaffolding, Learning devices, Advanced Calculus 1